PENGARUH PRODUCT KNOWLEDGE, PERCEIVED QUALITY, PERCEIVED RISK, DAN PERCEIVED VALUE TERHADAP PURCHASE INTENTION PADA MOTOR KAWASAKI NINJA 250 FI DI KOTA SEMARANG - Adi Kurniawan, Henricus; Indriani, Farida (Diponegoro Journal of Management, 2018)
This study aims to examine the factors affecting purchase intention. These factors are namely product knowledge, perceived quality, perceived risk, perceived value.The population in this study were all people who knew but had never bought a Kawasaki Ninja 250 Fi motorcycle product, who lived in Semarang City. The sample was selected  using  purposive  sampling  method.  Based  on  the  criteria  that  have  been determined, obtained a sample of 100 respondents.The data analysis technique used in this study is multiple linear regression. The results showed that product knowledge and perceived value had a positive and significant effect  on  purchase intention.  Meanwhile perceived  quality and  perceived  risk are not significant to purchase intention.